Physical and Sexual Violence Experienced by Male War-Affected Youth: Implications for Post-Conflict Functioning and Intimate Relationships - Alleyne-Green, Binta (Journal of interpersonal violence, 2021)
This study explored the association between war violence exposure during armed conflict and intimate partner violence (IPV) victimization, and the impact of positive community and family reintegration on IPV among a sample (N = 92) of war-affected male youth, post-conflict Sierra Leone. Trained Sierra Leonean researchers conducted face-to-face interviews with youth and their caregivers. Results indicate that exposure to violence during armed conflict as well as community and family reintegration were negatively associated with psychological IPV perpetration. Community reintegration was negatively associated with physical IPV. Sexual victimization was negatively associated with sexual IPV perpetration, whereas physical victimization had positive association. More research needs to be done on male war-affected youth as victims of physical, psychological, and sexual violence during conflict and the impact this has on the quality of their intimate relationships, occurrence of IPV in those relationships (as victims in addition to being perpetrators), and their community reintegration.